AI for social good: unlocking the opportunity for positive impact - Tomašev, N; Cornebise, J; Hutter, F; Mohamed, S; Picciariello, A; Connelly, B; Belgrave, DCM; Ezer, D; Haert, FCVD; Mugisha, F; Abila, G; Arai, H; et al. (Springer Nature, 2020)
Advances in machine learning (ML) and artificial intelligence (AI) present an opportunity to build better tools and solutions to help address some of the world’s most pressing challenges, and deliver positive social impact in accordance with the priorities outlined in the United Nations’ 17 Sustainable Development Goals (SDGs). The AI for Social Good (AI4SG) movement aims to establish interdisciplinary partnerships centred around AI applications towards SDGs. We provide a set of guidelines for establishing successful long-term collaborations between AI researchers and application-domain experts, relate them to existing AI4SG projects and identify key opportunities for future AI applications targeted towards social good.